IMPLEMENTATION OF GEOGRAPHY CURRICULUM AND LEARNING METHODS: A BIBLIOMETRIC ANALYSIS - Albertus Erico Jerry Krisna Nugroho; Sugiyanto Sugiyanto; Singgih Prihadi (Jurnal Eduscience, 2025)
Purpose – This study examines the execution of the geography curriculum and pedagogical strategies through a bibliometric analysis technique. By utilizing data from the Scopus database, the research identifies publication trends, thematic clusters, and key factors influencing the development of geography education.